Analisis Kinerja Perusahaan Asuransi Umum Nasional dan Perusahaan Asuransi Umum Patungan di Indonesia - Yohanes Jhony Kurniawan; Heppy Julianto; Suhartono Suhartono (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This analysis reflects the performance of National General Insurance Companies and Joint Venture General Insurance Companies in Indonesia. This allows this mapping to be used as a tool to analyze and control the performance of National General Insurance Companies and Joint Venture General Insurance Companies in Indonesia. So based on the above we will raise the research title "Performance Analysis of National General Insurance Companies and Joint Venture General Insurance Companies in Indonesia," This research aims; To find out the performance of National General Insurance Companies, to find out the performance of general insurance companies and joint venture general insurance companies in Indonesia, and to find out the differences in the performance of national general insurance companies and joint venture general insurance companies in Indonesia. This research method is quantitative descriptive. The conclusions are 1) Asset performance, equity performance, debt performance, revenue performance, cost performance, profit and loss performance, investment performance, technical reserve performance of joint venture general insurance companies have a tendency to increase from 2018 - 2022, while investment performance / technical reserves (%) Joint General Insurance has a downward trend from year to year from 2018 - 2022, 2.a) Asset Performance, Equity Performance, Debt Performance, Income Performance, Investment Performance, and Technical Reserve Performance of national general insurance has an upward trend from year to year 2018 - 2022, 2.b) but the performance of national general insurance costs has a tendency to fall from year to year from 2018 - 2022 then rises and then falls at the end of 2022, while the profit and loss performance of national general insurance has a tendency to be unstable from year to year from 2018 - 2022 with an upward trend, and Investment Performance / Technical Reserves (%) of national general insurance has a downward trend from 2018 - 2022, 3) The differences in the performance of National General Insurance Companies and Joint Venture General Insurance Companies in Indonesia are as follows; 1). Joint Venture General Insurance has better performance than national general insurance companies in; Asset performance, debt performance, cost performance, and investment performance / technical reserves (%), and 2) National General Insurance has better performance than joint venture general insurance companies from 2018 - 2022 in; Equity performance, income performance, profit and loss performance, investment performance, and technical reserve performance.